Pengaruh Dimensi Motivasi Belanja Hedonisme Konsumen Terhadap Impulse Buying Produk Fashion Secara Online pada Facebook - Putri Rahayu; Rose Rahmidani (Universitas Negeri Padang, 2022)
This study object to examine the effect of the hedonism shopping motivation dimension on impulse buying of fashion products online on Facebook in Padang City. This type of research is causative. The population in this study were women with certain criteria and had purchased fashion products without a plan on Facebook in Padang City. Samples were taken using the Cochran formula with 97 respondents and selected by purposive sampling technique. The type of data used in this study is primary data. The analytical method used is multiple regression analysis using SPSS version 21. The results of this study indicate that: 1) shopping adventures have a significant effect on impulse buying of fashion products online on Facebook in Padang City, 2) social shopping has a significant effect on impulse buying of fashion products online. online on Facebook in Padang City, 3) shopping gratification has a significant effect on impulse buying of fashion products online on Facebook in Padang City, 4) shopping ideas have a significant effect on impulse buying of fashion products online on Facebook in Padang City, 5) the role of shopping has an effect significantly to impulse buying of fashion products online on Facebook in Padang City, 6) the value of shopping has no significant effect on impulse buying of fashion products online on Facebook in Padang City.Keywords: impulse buying and hedonism shopping motivation